Improving the Performance of Hospital Employees Reviewed from the Perspective of Organizational Culture, Organizational Citizenship Behavior, and Organizational Commitment - Ningsih, Luh Kartika; Prastiwi, Ni Luh Putu Eka Yudi (International Journal of Social Science and Business, 2022)
Hospital becomes a place to get health facilities and services for people in need. especially in the current pandemic period, the existence of hospitals becomes an agency that is very calculated its existence. not only medical personnel play an important role but non-medical personnel also have their own contributions in supporting the service process in the hospital. This study aims to explore the Environmental Implications of Organization, Organizational Citizenship Behaviour (OCB), and Organizational Commitment to Employee Performance. The study used a quantitative approach, the number of samples used in the study as many as 58 employees. The data collection technique used in this study is in the form of questionnaires. Data analysis techniques used in this study are structural equation modelling (SEM) based on variance or component-based SEM, famously called Partial Least Square (PLS). There were 5 relationships examined in the influence of Organizational Culture on OCB (14,060 > 1,960), The Influence of OCB on Employee Performance (2,213 > 1,960), Organizational Cultural Influence on Organizational Commitment (12,516 > 1,960), organizational commitment influence on employee performance (3,783 > 1,960), organizational cultural influence on employee performance (19,293 > 1,960). All of the relationships studied showed positive and significant results, according to t-statistics > t-table (1,960). From the results of this study, it can be known that employee performance can be achieved if the conditions of the employees are in an optimal situation. Whether the individual condition of the employee itself, relationships with co-workers, the work environment or relationships between divisions established during the work process.